Microplot evaluation of the yield reduction potential of Pratylenchus coffeae, Helicotylenchus multicinctus, and Meloidogyne javanica on plantain cv. Apantupa (Musa spp., AABgroup) in Ghana - Brentu, C.F.; Speijer, P.R.; Green, K.R.; Hemeng, B.M.; Waele, D. de; Coyne, Danny L. (Brill, 2004)
The damage potential of the plant-parasitic nematodes Pratylenchus coffeae, Helicotylenchus multicinctus and Meloidogyne javanica, was assessed on plantain (Musa spp., AAB-group) cv. Apantu-pa in microplots in Ghana. Hot water treated suckers, planted in 3 l plastic bags containing sterilised soil, were inoculated 1 month after planting with a single nematode species or a nematode species mixture; controls were not inoculated. The initial single species inocula consisted of 1000 or 10 000 nematodes per plant, whilst the initial species mixture inoculum consisted of 3000 nematodes of each nematode species per plant. Two months after planting, the suckers were transplanted into micro-plots (0.7 m3 concrete containers filled with sterilised soil). Inoculation of single species at either density resulted in lower (P ≤ 0.05) bunch weights of the mother plants (between 23-33% lower) than the noninoculated control plants, whilst bunch weights of plants inoculated with the species mixture were 18% lower (P ≤ 0.05). Nematode damage indices (% dead roots, root necrosis and sucker corm lesions) were more severe in P. coffeae inoculated treatments. There was no difference between inoculated treatments and the control in plant growth parameters (days to flowering, number of standing leaves, height, girth, number of suckers) of the mother plant at flowering and harvest. Plant toppling occurred only in, and in all, treatments involving P. coffeae, with up to 60% of bunch-carrying plants toppled in the most affected treatment (inoculation of 10 000 nematodes per plant). Therefore, projected yields per ha were low in P. coffeae inoculated treatments: 41, 73 and 65% lower than the control for inoculation of 1000, 10 000 and 3000 (in species mixture) individuals, respectively. Inoculation with 10 000 H. multicinctus or M. javanica per plant resulted in yield losses of 26 and 30%, respectively. This study suggests that P. coffeae is likely to be the most important biotic constraint to plantain production in Ghana. Nematodes have been viewed as the major biotic constraint to plantain production in the country, and P. coffeae is the most widespread and abundant nematode species on plantain in Ghana. The results further demonstrate that H. multicinctus and M. javanica can cause considerable yield reduction in plantain.